(untitled) (Fisioterapia e Pesquisa, 2022)
This study aims to evaluate the effect oftranscutaneous auricular vagus nerve stimulation (taVNS) oninflammation, cardiac autonomic modulation, and clinical evolutionof patients with COVID-19. This is a clinical, sham-controlled,randomized, and blind trial, in which 52 hospitalized individualsdiagnosed with COVID-19 will participate. They will be randomizedinto: experimental group (usual medical treatment associatedwith active taVNS) and control group (usual medical treatmentassociated with sham taVNS). The taVNS will be performedby a neuromuscular electric stimulator (Dualpex model 071of Quark Medical Products), with the stimulation electrodepositioned on the left tragus, with alternating current, at a 30Hzfrequency with 50% variation. Intensity will be adjusted to thepatient’s sensory threshold, with 90-minutes-long stimulationsessions, happening twice per day for seven consecutive days,totaling 14 sessions. Interleukin-6 (IL-6) and interleukin-10 (IL-10),cortisol and C-reactive protein (CRP), blood pressure, heart ratevariability (HRV) by low frequency (LF), high frequency (HF)and low and high frequency ratio (LF/HF) parameters will beevaluated before and after the intervention, as well as patients’clinical evolution—including anxiety and depression levels—whose data will be obtained through medical records andquestionnaires. A follow-up will also be performed seven and14 days after the end of the interventions to verify the clinicalevolution, including anxiety and depression levels. Memory andattention levels will be evaluated for six months.